2021
DOI: 10.3390/su13147763
|View full text |Cite
|
Sign up to set email alerts
|

The Role of B Companies in Tourism towards Recovery from the Crisis COVID-19 Inculcating Social Values and Responsible Entrepreneurship in Latin America

Abstract: One of the particularities of companies with a social purpose is that, through their business model of B companies, they have incorporated into their processes the necessary mechanisms to obtain, simultaneously, the profits to ensure the existence of the organization in the market. At the same time, social value is generated, which is necessary to address the problems of the social crisis caused by COVID-19 and the environmental problems affecting the community. The current global health and economic crisis ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 113 publications
(138 reference statements)
0
13
0
1
Order By: Relevance
“…Women's way of thinking differs from men's on the basis of some distinctive characteristics, such as their more resilient, equanimous, consensual, and mediating sense of leadership [58]. In addition, they are characterized by their ability to propose strategies that enable them to significantly contribute to the achievement of management results in companies and to successfully contribute to the achievement of strategic and corporate sustainability objectives [59,60].…”
Section: Discussionmentioning
confidence: 99%
“…Women's way of thinking differs from men's on the basis of some distinctive characteristics, such as their more resilient, equanimous, consensual, and mediating sense of leadership [58]. In addition, they are characterized by their ability to propose strategies that enable them to significantly contribute to the achievement of management results in companies and to successfully contribute to the achievement of strategic and corporate sustainability objectives [59,60].…”
Section: Discussionmentioning
confidence: 99%
“…The bibliometric and scientometric analysis of trail tourism presented here establishes the role of the entities in this field (individuals, groups and institutions) with respect to affiliated articles that today show a high growth in knowledge management with quantity, quality and thematic maturity, achieving criticism in the scientific mass [ 68 , 81 ]. The work developed in this article provides an overview of academic research showing part of a universe of knowledge on hiking [ 8 , 21 , 25 , 82 ]. A first finding evidences 820 articles published in the main science database WOS, showing an upward trend for hiking in scientific production worldwide from 1991 to 2022.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that only through collaboration can the sector overcome challenges and seize new opportunities [ 8 ]. The UNWTO, by bringing together the will of the tourism community and offering concrete measures, has guided the tourism response with the aim of not only reviving the sector, but also making it increasingly inclusive, innovative and sustainable [ 21 ]. For this organization, mountain or trekking tourism is a type of tourism activity that takes place in a defined and delimited geographical space such as hills or mountains, with characteristics and attributes inherent to a given landscape, topography, climate, biodiversity (flora and fauna) and the local community, encompassing a wide range of outdoor leisure and sport activities [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…According to [24], cinema, like any other cultural industry, consists of the design, production, and commercialization of manufactures destined to the transmission of symbolic contents, whose activities are conditioned by the systems of the economic, cultural, and political conditions of each country, and interrelated with the industries dedicated to culture, social communications, and entertainment. For its part, marketing plays an important role in the opening weekend of a movie, so the consumer's perceived value and benefits of watching a movie at the cinema will determine their purchase intention [9,25].…”
Section: Background 21 Sustainable Purchase Intention and Cinemamentioning
confidence: 99%
“…It usually refers to an individual's willingness to perform a specific act, which is perceived as the premise for direct action [29,30]. Therefore, understanding people's intentions and the reasons they are willing to use a product or service is critical for marketers and marketing stakeholders [25,26]. In addition, intentions capture the motivational factors that influence a behavior, in other words, they indicate how much people are willing to try and how much effort they plan to make to perform a certain behavior [9].…”
Section: Background 21 Sustainable Purchase Intention and Cinemamentioning
confidence: 99%